Business pricing and inflation - "Sawyer,Malcolm C" (London, 1983)
This book probes some of the theoretical and empirical aspects of inflation, focussing particularly on the deternination of changes in output prices. It argues that the causes of inflation should be discussed within a framework which incorporates conflict over income shares. Firms aim for increases in profits, and workers for increases in real wages, and there is no strong reason to think that those increased claims are compatible.
Keywords: Economic theory